"Not Tied Up Neatly with a Bow": Professionals' Challenging Cases in Informed Consent for Genomic Sequencing. Issue 1 (26th April 2015) - Tomlinson, Ashley N.; Skinner, Debra; Perry, Denise L.; Scollon, Sarah R.; Roche, Myra I.; Bernhardt, Barbara A.
Abstract: As the use of genomic technology has expanded in research and clinical settings, issues surrounding informed consent for genome and exome sequencing have surfaced. Despite the importance of informed consent, little is known about the specific challenges that professionals encounter when consenting patients or research participants for genomic sequencing. We interviewed 29 genetic counselors and research coordinators with considerable experience obtaining informed consent for genomic sequencing to understand their experiences and perspectives. As part of this interview, 24 interviewees discussed an informed consent case they found particularly memorable or challenging. We analyzed these case examples to determine the primary issue or challenge represented by each case. Challenges fell into two domains: participant understanding, and facilitating decisions about testing or research participation. Challenges related to participant understanding included varying levels of general and genomic literacy, difficulty managing participant expectations, and contextual factors that impeded participant understanding. Challenges related to facilitating decision‐making included complicated family dynamics such as disagreement or coercion, situations in which it was unclear whether sequencing research would be a good use of participant time or resources, and situations in which the professional experienced disagreement or discomfort with participant decisions. The issues highlighted in these case examples are instructive in preparing genetics professionals to obtain informed consent for genomic sequencing.